基于路况效应的重型载货汽车桥壳有限元分析 - 姜无疾 (Jixie chuandong)
To further study the drive axle housing operating characteristic of heavy truck,by using finite element method,Miner linear damage accumulation theory,Goodman principle and the effect of the road,the further analysis of the conditions that fit the actual working conditions,the variation law of stress,deformation and life and safety coefficient of the drive axle housing of heavy truck under the actual road is studied.The results show that,through re-calculation model SN curve correction and import the effect of the road load spectrum,the drive axle housing performance calculation parameters of this type of heavy truck and the actual product bench test results are the same,the regularity maximum stress is exist in the drive axle housing parts of heavy truck,the first six axle natural frequencies are far away from the actual working conditions of road excitation frequency,the most injuries of the drive axle housing of heavy truck occur under high stress amplitude and the fatigue life satisfies the requirement of enterprise.